college algebra

posted by .

what is the x value of the vertex

f(x)=x^2+6x+5 my answer is -3 is the correct

  • college algebra -

    correct

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    How do you get the vertex of this absolute value?
  2. Algebra

    Write an equation for the translation so the graph has the given vertex. 1. y=-|x| vertex (-5,0) 2. y=2|x| vertex (-4,3) 3. y=-|x| vertex (p,q) I really have no idea how to even begin these, but I do know the answer to # 2 is y=2|x|+11 …
  3. Algebra

    Find the vertex of the functions given below. 1. y=(x-4)(x+2) 2. y=2x^2-4x+1 The midpoint of the x-intercepts of a parabola has the same x value as the vertex. the x-intercepts are obviously x=4 and x=-2 so the x value of the vertex …
  4. Algebra

    Can someone tell me if I am right? I need to find the equation of a parabola. I am not sure if this is the correct way or if I have the correct answer. Vertex at origin, focus is at (0,3) Equation of parabola vertex (0,0) focus (0,3)
  5. Algebra 2

    Hey I am working on math homework that involves "Standard Form to Vertex Form by Averaging." My class is just starting to learn this today, but I am totally lost still on what to do. Can you please help?
  6. college algebra

    what is the y value of the vertex f(x)=x^2+6x+5 I have an answer of 4 this is important because I come up with -4 and I believe the answer to this is 4
  7. college algebra

    find the vertex f(x)=3x^2-6x+8 I have an answer of -1 and 17 I believe that the correct answer is 1,5 is this correct
  8. college algebra

    find the vertex of f(x)=3x^2-6x+8 i have an answer of (1,-5) or is the correct answer (1,5)
  9. college algebra

    find the vertex of f(x)=3x^2-6x+8 i have an answer of (1,-5) or is the correct answer (1,5)
  10. Algebra

    For the given quadratic equation convert into vertex form, find the vertex, and find the value for x = 6. Show your work. y = -2x2 + 2x +2 -(1/2)y = x^2 - x - 1 (-1/2)y + 1 = x^2 - x (-1/2)y + 1 = (x - 1/2)^2 - 1/4 (-1/2)y = (x-1/2)^2 …

More Similar Questions